Design and Analysis Fixtures for Aluminium Die Casting Component (International Journal of Innovative Research in Computer Science & Technology, 2017)
Fixture in tooling industry contributes more  to improve economy of production. It ensures quality  and quick transition of parts. A novel design on a  fixture for tapping holes for complicated profile petrol  pump body made of aluminium die casting material.  The fabricated fixture used for trials. The time study  conducted with samples and the results we compared  with manual cycle time. Improvement in reduced  cycle time shown 50% and the rejection quantity due  to unmatured threads, shifting of axis and end damage  are reduced 1/50 batch. Fixtures like this can adopt to  the mass production components in automobile,  Aeronautics and manufacturing units.
Keywords: fixtures; aluminium; tapping; production